Senior High School English Teaching: Policy Implementation, Future - Sjafty Nursitti NP Maili; Dewi Mutiara Indah Ayu; Endang Sondari (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
Curriculum changes in essence the goal is very noble and namely in an effort to improve the quality of education in a better direction than before. But in fact, curriculum changes affect the policies made, as well as the application of learning in every unit of education ranging from elementary school level (elementary) to junior high school and high school level. The application of English learning at Senior High School has been applied in schools from the era after Independence Day. There are also problems caused by the new policy, the application of English learning in the classroom. This research aims to describe the policies, the application of English learning at Senior High School level, and the solution in the future. The method used is a literature approach, analyzing the theory read, then concluded.